PENGARUH PENGGUNAAN MEDIA JIGSAW PUZZLE PADA MATERI SILA-SILA DALAM PANCASILA TERHADAP KEMAMPUAN GOTONG-ROYONG SISWA KELAS II DI SDN SUKUN 2 MALANG - Oktaviana Juita; Romia Hari Susanti; Yulianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the decline in mutual cooperation values among ele- mentary school students as a result of increasingly individualistic attitudes in the digital era. The purpose of this study was to examine the effect of using jigsaw puz- zle media on Pancasila principles material on the mutual cooperation ability of sec- ond-grade students at SDN Sukun 2 Malang. This research employed a quantitative approach with a quasi-experimental design using a One Group Pretest–Posttest Design. The participants consisted of 28 second-grade students selected through saturated sampling. Data were collected through observation using an attitude as- sessment instrument that had been validated and tested for reliability, with a Cronbach’s Alpha coefficient of 0.870. Data analysis techniques included normality testing, homogeneity testing, and the Wilcoxon Signed Rank Test using SPSS Sta- tistics. The results showed that both pretest and posttest data were not normally distributed, with significance values of 0.039 and 0.017, respectively, and the data were not homogeneous, with a significance value of 0.030. The Wilcoxon Signed Rank Test produced a Z value of −4.630 with a significance level of 0.000 (p < 0.05), indicating that the null hypothesis was rejected. These findings demonstrate that the use of jigsaw puzzle media has a significant effect on students’ mutual cooperation ability, particularly in the indicators of helping each other, respecting cooperation, solidarity, and voluntariness. The jigsaw puzzle media provides meaningful collab- orative learning experiences that encourage students to actively practice mutual co- operation values through structured group activities.